Charged Particles Moving around a Spherically Symmetric Dilatonic Black Hole - Vitalie Lungu; Marina–Aura Dariescu; Ciprian Dariescu; Cristian Stelea (Advances in High Energy Physics)
For the static spherically symmetric dilatonic black hole described by the Gibbons–Maeda–Garfinkle–Horowitz–Strominger geometry, we analyze the timelike trajectories for electrically charged test particles. Both cases of an electric black hole and a magnetic one are considered. Finally, we are obtaining the solution to the Klein–Gordon equation in terms of Heun confluent functions and the corresponding energy spectrum. A special attention is given to the role of the dilaton parameter.